Percepções de estudantes sobre a interação como elemento da distância transacional por meio de ambientes sociais digitais no ensino híbrido - Wajnsztejn, Marina (2022)
This research aims to reflect on how interactions, in social digital environments, serve as positive mediation and a way of decreasing transactional distance. This study includes a historical moment that comprises the covid-19 pre-pandemic period and the pandemic itself. From an academic point of view, the research is justified by the fact that technology, adopted on an emergency basis, offers new learning ways and changes cognitive processes. It focuses to answer the following problematic question: how to expand students’ perception that interactions in social digital environments reduce transactional distance? The guiding hypothesis assumes the effectiveness of interactions in social digital environments as a tool to reduce transactional distance. The study is based on qualitative research methodology, experimental type, based on data collected in the field. Literature review includes two periods for each phase of the study. Pre-pandemic phase contains studies published from 2015 to 2019 and pandemic phase contemplates studies published from 2020 to 2021, both composed of articles, theses and dissertations from the institutions PUC Banco de Teses, Capes, SciELO and Google Scholar. Instruments for data collection are questionnaires, observation and in-depth identification. Theoretical framework for this study includes concepts such as digital culture and education. Digital culture context is based on Gere (2008). In the field of education, we focus on the fundamentals of connectivism by Siemens (2004), on the transactional distance of Moore (2002) and on the discussion about hybrid education. The research context involves, in different phases, 500 students from the Escola Superior de Propaganda e Marketing, in São Paulo, enrolled in the Advertising course. As a final conclusion, this research draws a hybrid teaching framework and contributes to broaden the debates that include the learning process in its context. As suggestions for future studies, we consider it worthy to review the processes of the educational field focusing on the establishment of a common definition of blended learning and their different approaches suggested on the framework proposal